PERANCANGAN SISTEM INFORMASI PENYALURAN BERAS (RASKIN) PADA DESA BALONGGANDU JATISARI - Yuli Komalasari; Dede Firmansyah; Riska Rachmania Agatha; Diah Wijayanti (Universitas Islam Kuantan Singingi, 2020)
The problem of poverty is one of the fundamental problems that is the center of attention of the government in any country. Government programs used to tackle poverty are Raskin (Rice for poor families) organized by BULOG. The Raskin program (distribution program for poor families) is a program from the Government. The program is an effort to reduce the burden of disbursement from poor households as a form of support in improving food security by providing social protection of cheap rice with a maximum of 15kg / poor household / month with each price Rp.1.600,00 per kg (net ) at the distribution point. In this case the distribution mechanism of poor rice distribution in the village of Kosar there are still many processes that have problems such as data collection recipients of rice raskin are still classified as less effective as in the recording of recipients RASKIN, still conventional. This causes the vulnerable data to be lost or corrupted. As well as data processing using Microsoft Excel, if the device used damaged data lost and no data backup, data processing must be repeated again. the information system of Raskin rice distribution effectively and efficiently and make it easier for the staff so that they can achieve the competitive advantage. The system can be developed and applied in fields that require computerization of existing data. the information system of Raskin rice distribution effectively and efficiently and make it easier for the staff so that they can achieve the competitive advantage. The system can be developed and applied in fields that require computerization of existing data.